PREPARING A FUTURE TEACHER FOR FORMATION OF PRIMARY SCHOOL STUDENTS CULTURES OF INTERNATIONAL NATIONAL COMMUNICATION - T.O. Antroshchenko (Academy of Cognitive and Natural Sciences, 2004)
The preparation of the future teacher for the forming of the culture of international communication in the pupils of the elementary school. This article examines the problem of the preparation of the future teacher for the forming of a culture of international communication in the pupils of the elementary school. This article denotes the forms and methods which provide the effective decision of this problem and accompanies the scientific-teacher process in the elementary school.